HDL-free cholesterol influx into macrophages and transfer to LDL correlate with HDL-free cholesterol content - Dedipya Yelamanchili; Baiba K. Gillard; Antonio M. Gotto, Jr.; Miguel Caínzos Achirica; Khurram Nasir; Alan T. Remaley; Corina Rosales; Henry J. Pownall (Journal of Lipid Research)
High-density lipoprotein (HDL)-free cholesterol (FC) transfers to other lipoproteins and cells, the former by a spontaneous mechanism and the latter by both spontaneous and receptor-mediated mechanisms. Macrophages are an important cell type in all stages of atherosclerotic cardiovascular disease (ASCVD), and the magnitude of FC efflux from macrophages to HDL, a metric of HDL function, inversely associated with several metrics of ASCVD. Very high plasma HDL concentrations are associated with increased all-cause and ASCVD mortality, suggesting that the reverse process, FC influx from HDL into macrophages, is atherogenic. We hypothesize that HDL-FC is a metric of dysfunctional HDL, and when combined with HDL particle number (HDL-P), is an ASCVD risk factor. The magnitude of FC influx from HDL to macrophages is expected to be a function of HDL-P and HDL-FC content. Here we show that plasma HDL-FC content varies 2-fold among normolipidemic human subjects and linearly correlates with low-density lipoprotein (LDL)-FC content. The influx of HDL-FC into macrophages and transfer to LDL increase linearly with HDL-FC. As expected, the influx of HDL-FC into macrophages and the transfer to LDL are positively correlated. These data support the hypothesis that high HDL FC content is a marker for dysfunctional HDL, resulting in greater influx into macrophages and greater HDL-FC transfer to LDL. HDL-FC transfer to LDL is a valid surrogate for influx into macrophages. This study of HDL composition and function of normolipidemic subjects provides the basis for further investigation and establishment of HDL-FC content as an ASCVD risk factor.